Toward a non‐invasive inuit polar bear survey: Genetic data from polar bear hair snags. (30th April 2013) - De Groot, Peter Van Coeverden; Wong, Pamela B. Y.; Harris, Christopher; Dyck, Markus G.; Kamookak, Louie; Pagès, Marie; Michaux, Johan; Boag, Peter T.
Abstract We explore the feasibility of collecting microsatellite genotypes of non‐invasively collected hair from free‐ranging polar bears (Ursus maritimus) in M'Clintock Channel, Nunavut, Canada. We estimate the minimum number of individuals in a region of the M'Clintock Channel population and evaluate potential sampling biases associated with corral sampling stations. We optimized 6 variable microsatellite loci for genotyping hair‐snag DNA with low genotyping error (mean allelic dropout and false allele error rates <5%). In May of 4 sequential years (2006–2009), we collected 595 hair‐snag samples from 145 baited corral sampling stations, from which 319 hair snags were used to detect 59–82 individuals using 4–6 microsatellite loci; we also genetically sexed these individuals. Although genetic sex estimates of matching genotypes are generally in agreement, the estimated sex ratio differs from that previously reported from aerial mark–recapture, which suggests a potential male bias in our sampling stations. These noninvasive methods of identifying individual and sex of bears hold promise for frequent and inexpensive estimates of polar bear population activity informed by Inuit hunters. © 2013 The Wildlife Society.